Empowerment Pattern of Farmer In Husoak Village, Hubikiak Districk, Through Strengthening of Farmer Group Resouces - Tuhuteru, Sumiyati; Mahanani, Anti Uni; Rumbiak, Rein Edward Yohanes (Amalee: Indonesian Journal of Community Research and Engagement, 2023)
Many farmer groups in the community still need legal institutions, especially in the Central Highlands Region of Papua. Thus, this empowerment activity is carried out to optimize the resources of the members of the farmer groups that have been formed and explain the importance of the existence of a farmer group in the development of farming and livestock owned. The community service initiative employs the Community Based Research (CBR) methodology, specifically using the Forum Group Discussion (FGD) technique for training and mentoring. The results of the implementation of this activity were that the Bisimo Etaikena farmer group was required to have an administrative system starting from farming planning, documentation, or recording of group farming processes and results (both agricultural and livestock cultivation), and the ability to process agricultural products that had to be carried out, to help improve welfare—farmers in a structured manner and not only in obtaining government assistance.